2008
DOI: 10.1097/qai.0b013e318189a769
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Initiating Highly Active Antiretroviral Therapy in an Integrated Antenatal and HIV Clinic in Johannesburg, South Africa

Abstract: Objective To describe the safety and efficacy of highly active antiretroviral therapy (HAART) in pregnant women treated in an integrated antenatal antiretroviral programme (ANC ARV). Methods A retrospective analysis was performed on patients attending the ANC ARV from August 2004 through February 2007. Results Data was collected on 689 treatment-na誰ve pregnant women initiated on HAART. The mean age was 29.2 years. The mean baseline CD4+ count was 154 cells/uL and mean baseline HIV viral load was 101,561 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…The remaining 35 full text articles were assessed for eligibility: 29 were excluded because the study's intervention did not meet the definition used in this review; 2 more studies 27,28 were excluded because they lacked a comparator arm (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 35 full text articles were assessed for eligibility: 29 were excluded because the study's intervention did not meet the definition used in this review; 2 more studies 27,28 were excluded because they lacked a comparator arm (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…44,45 Indeed, in an integrated South African ANC clinic, fewer than 1% of the women who had been on ART for at least 7 weeks during pregnancy transmitted HIV to their infants. 28 Therefore, optimizing service delivery by minimizing the number of clinic visits and the number of weeks that transpire before initiating ART could reduce losses to care and the risk of vertical HIV transmission. Although the process for delivering ART to eligible pregnant women varies, it generally involves: (i) attendance at an ANC clinic; (ii) provider-initiated HIV testing and counselling; (iii) referral to an HIV clinic; (iv) enrolment in care at the HIV clinic; (v) assessment of eligibility for ART (based on CD4+ Tlymphocyte count and/or WHO clinical stage); (vi) initiation of ART if eligible, and (vii) maintaining high adherence to ART and life-long retention in HIV treatment and care (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries nevirapine (NVP) is the most frequently used drug to prevent vertical transmission. 1 During the last decade studies from different regions in the world reported conflicting results on the risk on mainly NVP-related liver toxicity in pregnant women. 1e10 One of the possible risk factors of hepatotoxicity is a CD4 þ cell count >250 cells/ml.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Research and programmes from resource-limited settings have largely focused on short-course regimens of antiretrovirals in pregnancy, with the objective of reducing MTCT, but data are gradually emerging from cohorts of women from these settings receiving HAART. [5][6][7] That a woman should receive HAART if it is indicated for her own health is not controversial. Benefits to a woman's health clearly outweigh the known or theoretical risks associated with antiretroviral use, and her health and survival are paramount.…”
Section: Hiv I-base Ukmentioning
confidence: 99%